2000
DOI: 10.1007/3-540-45035-1_5
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylcholine-Preferring Phospholipase C from B. cereus. Function, Structure, and Mechanism

Abstract: The PLC class of enzymes has been studied extensively over the past 15-20 years because of their involvement in signaling pathways in which extracellular messages are delivered to the cell to induce a response. Of the PLC isoenzymes, the PI-PLCs have perhaps been examined in the greatest detail because of their key role in initiating cellular response by hydrolyzing the phosphodiester bond of phosphatidylinositols and their phosphorylated derivatives to release the second messengers IP 3 and DAG. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 114 publications
0
14
0
Order By: Relevance
“…Similar results were recorded by other researchers; Wang et al [37] found the maximum activity of PLC from B. mycoides to be at pH 7.0 -7.5. Hergenrother and Martin [5] reported that the optimal pH for activity of Bacillus cereus PLC was 8, while Otnaess et al [75] proved that the variation of pH from 7.2 to 8.3 affected neither activity nor substrate specificity of purified PLC from Bacillus cereus and the highest activity occurred at 37 to 60°C. Vis-à-vis, Durban et al [64] stated that the highest activity of PLC in the culture supernatants of 12 strains of Bacillus cereus against p-nitrophenylphosphorylcholine was at an acidic pH between 3.5 and 6 at 20 to 60°C.…”
Section: Enzymatic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were recorded by other researchers; Wang et al [37] found the maximum activity of PLC from B. mycoides to be at pH 7.0 -7.5. Hergenrother and Martin [5] reported that the optimal pH for activity of Bacillus cereus PLC was 8, while Otnaess et al [75] proved that the variation of pH from 7.2 to 8.3 affected neither activity nor substrate specificity of purified PLC from Bacillus cereus and the highest activity occurred at 37 to 60°C. Vis-à-vis, Durban et al [64] stated that the highest activity of PLC in the culture supernatants of 12 strains of Bacillus cereus against p-nitrophenylphosphorylcholine was at an acidic pH between 3.5 and 6 at 20 to 60°C.…”
Section: Enzymatic Propertiesmentioning
confidence: 99%
“…Bacillus PLC is a 28.5 kDa enzyme whose structure has the three important features, the Zinc (Zn) centre consisting of three Zn ions that are all pentacoordinate; the choline binding site which is the substrate binding cleft that accommodates the choline headgroup and is lined with Glu4, Asp55, and Tyr56; and the lipid binding site [5]. In B. cereus group species, the transcriptional regulator PlcR (Phospholipase C Regulator) controls PLC production [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the L. monocytogenes broad-range PLC was cloned, expressed as an intein fused protein in Escherichia coli , purified, and characterized in an active and homogeneous form. Lm PLC orthologues from other Gram-positive bacteria, in particular the broad-range phospholipase C from Bacillus cereus ( Bc PLC) [11] and alpha-toxin from Clostridium perfringens [12], have been extensively characterized. Lm PLC shares considerable sequence (38.7%) and functional identity with Bc PLC, which binds three Zn 2+ ions at the enzyme active sites.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of DAG to induce nonbilayer phases is of crucial importance to its biological functions (Das and Rand, 1986). DAG is produced in the cell by phospholipase C via lipid hydrolysis (Hergenrother and Martin, 2001). The initial increase in DAG levels has been associated with the activity of the phosphatidylinositol-specific phospholipase C (PI-PLC) (Galneder et al, 2001), whereas prolonged elevation in DAG concentration is caused by the phosphatidylcholinepreferring phospholipase C (PC-PLC) (Exton, 1990).…”
Section: Introductionmentioning
confidence: 99%